Cobalt-Catalyzed Decarboxylative Methylation and Ethylation of Aliphatic N-(Acyloxy)phthalimides with Organoaluminum Reagents - Wang, Ze-Zhong; Wang, Guang-Zu; Zhao, Bin; Shang, Rui; Fu, Yao (Synlett, 2020)
A cobalt-catalyzed decarboxylative methylation of aliphatic redox-active esters [N-(acyloxy)phthalimides; RAEs] with trimethylaluminum under mild conditions was developed, providing a method for transforming a carboxylate group into a methyl group without redox fluctuation. Primary and secondary RAEs were both amenable substrates, whereas a tertiary RAE delivered an elimination product. Triethylaluminum was also used to deliver a decarboxylative ethylation product.
Keywords: cobalt catalysis; decarboxylative methylation; ethylation; trimethylaluminum; redox-active esters